Association of physical activity and sedentary behavior at school with cardiovascular risk factors in adolescents - Priscila Cristina dos Santos; Luiz Rodrigo Augustemak de Lima; Bruno Gonçalves Galdino da Costa; Cilene Rebolho Martins; Giseli Minatto; Juliane Berria; Everson Araújo Nunes; Edio Luiz Petroski; Kelly Samara da Silva (Universidade Federal de Santa Catarina, 2020)
The association of moderate to vigorous physical activity and sedentary behavior performed in the school context with cardiovascular risk factors is unclear. Thus, the purpose of this study was to evaluate whether MVPA and SB during school time are associated with single and clustered cardiovascular risk factors in 10- to 16-year-old school students. This study used the baseline data from a non-randomized controlled clinical trial ("MEXA-SE") conducted on 6th to 9th-grade students from schools in Florianopolis, Brazil. Skinfolds, resting blood pressure, 20-m shuttle-run test, fasting glucose, triglycerides, total cholesterol, high-density lipoprotein cholesterol, and white blood cell counts were obtained. MVPA and SB were objectively measured with accelerometers. A minimum of 180 minutes was considered valid school-time for analysis. Multiple linear regression adjusted for age, sex and habitual physical activity was used. School-time MVPA was positively associated with the peak VO2 (β = 0.17 ml.kg.min-1), and inversely associated with sum of four skinfolds (β = -0.96 mm), diastolic blood pressure (β = -0.36 mmHg), systolic blood pressure (β = -0.301 mmHg); triglycerides (β = -1.49 mg.dL-1), and clustered cardiovascular risk factors (β = -0.123). School-time SB was positively associated with clustered cardiovascular risk factors (β = 0.033). In conclusion, independently of habitual physical activity level, school-time MVPA and a lower time in SB were associated to single and clustered cardiovascular risk factors. Thus, the promotion of strategies aimed increase MVPA and reduce SB at school may prevent the onset and early accumulation of cardiovascular risk factors in adolescence.